Meaning and Vision of Mimic Computing and Mimic Security Defense - Jiangxing Wu (Dianxin kexue, 2014)
To facilitate high-performance and high-security computing, a technology system based on mimic computing（MC）and mimic security defense（MSD）was proposed. The proposed system focused on both the multi-dimensional reconfigurable and functional architecture and the dynamic varied mechanism. An overview about the concept and mechanism of the MC and MSD was also introduced from the angles of meaning and vision. The science and engineering problems to be further addressed were given in the end.